Religious experience and development of ethical values (A life of Muhammad ﷺ and psychology) - Saeed-Ur-Rehman, Dr. Muhammad; Amjad , Muhammad (Al-Amīr Research Journal for Islamic Studies, 2024)
This paper explores the intersection of religious experience and the development of ethical values, specifically through the lens of the life of Muhammad ﷺ and psychological perspectives. Religious experience, as articulated by scholars like John Hick and Chad Meister, is a universal and transformative phenomenon. The study delves into the neuro-scientific perspectives on religious experiences, examining their potential neurophysiological underpinnings. The religious personality in Islam, as discussed by Dr. Aisha Sitwat and Ms. Rabia Dasti, encompasses both ritualistic worship and ethical behavior inspired by Islamic teachings. Western perspectives on ethical development and the fundamental principles of Islamic ethics are also explored. The study highlights the integration of religious and ethical dimensions in Islam, emphasizing the comprehensive nature of Islamic spirituality and its implications for cognitive and behavioral practices. Key words: Religious experience, ethical values, Muhammad ﷺ, neuroscience, Islamic ethics, religious personality, cognitive behavior therapy, Five Pillars of Islam.